Relationship between methodology and academic performance in students of the basic english course at the National University of Education Enrique Guzman y Valle, Lurigancho-Chosica, Lima, 2014 - Oriondo Gates, Carmen Evarista (2015)
The thesis entitled RELATIONSHIP BETWEEN METHODOLOGY AND ACADEMIC PERFORMANCE IN STUDENTS OF THE BASIC ENGLISH COURSE AT THE NATIONAL UNIVERSITY OF EDUCATION ENRIQUE GUZMÁN Y VALLE, LURIGANCHOCHOSICA, LIMA, 2014, had as hypothesis that methodology is significantly related to the academic performance of the students of the Basic English Course at the National University of Education Enrique Guzmán y Valle, Lurigancho-Chosica, Lima in 2014. This research has been descriptive-quantitative with a correlational design. The population and sample were 75 students who studied English as a course within the curricula to obtain the degree of Bachelor in Educational Sciences with mention in two languages, being one of them English. After processing the results and performing the adequate testing, the hypothesis was found to be true, confirming that methodology is significantly related to the academic performance of the students of the sample with a significance level of 0,05.